Association of Total Fluid Intake and Output with Duration of Hospital Stay in Patients with Acute Pancreatitis. (2nd May 2018) - Koop, Andree H.; Stancampiano, Fernando F.; Jackson, Jillian; Henry, April; Horsley-Silva, Jennifer; Pannala, Rahul; Heckman, Michael G.; Diehl, Nancy N.; Palmer, William C.
Abstract : Background/Aims . The aim of this study was to evaluate the association of fluid balance with outcomes in patients hospitalized with acute pancreatitis (AP). Methods . This was a retrospective study of patients hospitalized between May 2008 and June 2016 with AP and a clinical order for strict recording of intake and output. Data collected included various types of fluid intake and output at 24 and 48 hours after admission. The primary outcome was length of stay (LOS). Analysis was performed using single-variable and multivariable negative binomial regression models. Results . Of 1256 patients hospitalized for AP during the study period, only 71 patients (5.6%) had a clinical order for strict recording of intake and output. Increased urine output was associated with a decreased LOS at 24 and 48 hours in univariable analysis. An increasingly positive fluid balance (total intake minus urine output) at 24 hours was associated with a longer LOS in multivariable analysis. Conclusions . Few patients hospitalized for AP had a documented order for strict monitoring of fluid intake and output, despite the importance of monitoring fluid balance in these patients. Our study suggests an association between urine output and fluid balance with LOS in AP.